2017
DOI: 10.1111/jcpt.12637
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐related problems identified during medication review before and after the introduction of a clinical decision support system

Abstract: The introduction of CDSS to medication review software generated additional DRPs with a lower resolution rate. Structural assessment including a patient interview elicited the most relevant DRPs. Further development of CDSS with more specific alerts is needed to be clinical relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…A possible explanation might be that more potential DRPs were identified by adding the computer‐assisted evidence based explicit criteria to the assessment by the pharmacist. Another explanation might be the use of a standardized patient questionnaire to inventory the drug utilization experience of patients instead of a patient interview by pharmacists with relatively little experience with performing patient‐interviews in the context of a medication review in the study of Geurts et al The comparable rate of resolved DRPs in our study despite the higher number of potential DRPs per patient, might be explained by: (i) a shorter follow‐up time in our study; and (ii) the fact that DRPs identified by clinical decision support are considered to be less relevant by physicians and patients …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…A possible explanation might be that more potential DRPs were identified by adding the computer‐assisted evidence based explicit criteria to the assessment by the pharmacist. Another explanation might be the use of a standardized patient questionnaire to inventory the drug utilization experience of patients instead of a patient interview by pharmacists with relatively little experience with performing patient‐interviews in the context of a medication review in the study of Geurts et al The comparable rate of resolved DRPs in our study despite the higher number of potential DRPs per patient, might be explained by: (i) a shorter follow‐up time in our study; and (ii) the fact that DRPs identified by clinical decision support are considered to be less relevant by physicians and patients …”
Section: Discussionmentioning
confidence: 73%
“…Tools used to perform a medication review can be based on implicit or explicit criteria (or a combination). Explicit criteria are evidence based and/or guideline based criteria to identify inappropriate medication, whereas implicit criteria are criteria to identify DRPs based on knowledge of the healthcare practitioner that performs the medication review . Examples of explicit criteria are the Beers and START (screening tool to alert doctors to the right treatment) and STOPP (Screening Tool of Older Persons potentially inappropriate Prescriptions) criteria .…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently cited causes of preventable ADRs included failure to recognise previously documented allergic reaction to the causative drug, drug-drug interactions overlooked, and inappropriate selection of medication and/or dosage for patients' clinical condition (e.g., comorbidity, age) [23,27,31,43]. Several initiatives have been performed to potentially reduce preventable medication harm in the primary care setting, including pharmacists-led medication review [75][76][77][78], clinical decision support (CDS) embedded in information system [79,80], educational intervention [81,82], and nurse-led medication monitoring, particularly in long-term care facilities [83][84][85].…”
Section: Plos Onementioning
confidence: 99%
“…3 43 This stresses the importance of DRP detection before dispensing the product to the patient, thereby promoting the minimisation of harms resulting from the medication process, 8 28 since computer system alerts issued for MO revision do not seem sufficient to guarantee the effectiveness of the pharmaceutical interventions. 44 A strength of the present study is the extended period of observation that allows the exclusion of the seasonality bias due to changing diseases characteristic throughout Open access the year. A major feature of the study was to perform MO review in all patients admitted to all departments of a general hospital, thus providing a better insight into the size and extent of DRP in a health facility as a whole than is provided by a study in particular populations or in specialised departments.…”
Section: Open Accessmentioning
confidence: 99%